The Physical Basis of Biochemistry The Foundations of Molecular Biophysics - Bergethon, Peter R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The Physical Basis of Biochemistry is an introduction to the philosophy and practice of an interdisciplinary field in which biological systems are explored using the quantitative perspective of the physical scientist. As with the first edition, the idea that a fundamental understanding of the basic physical principles underlying chemical biological systems is vital remains the focus of this second edition. This new edition of The Physical Basis of Biochemistry has substantial new material added with respect to models at the simple molecular level (including van der Waals gases and virial treatments) which is tied to coverage of models of polymer thermo-dynamics. The second edition is partitioned into five sections: the central concept that science is a way of looking at the world; the physical under-pinnings of biophysical chemistry with an emphasis first on energy, work and forces of biological importance; exploring how models applicable to molecular biophysics are constructed; the three-dimensional potential energy surface put into motion; and a succinct discussion of the bio-physical methods used to evaluate structure and function in biological systems. Additionally, a section of appendices continues to serve the pur¬pose of presenting some review information and certain topics in detail. The Physical Basis of Biochemistry will be of interest to quantitatively-oriented biologists as well as aspiring chemists, physicists, and engineers with an interest in biological systems.
Principles of Biophysical Inquiry -- Introduction: To the Student – First Edition -- Philosophy and Practice of Biophysical Study -- Overview of the Biological System Under Study -- Physical Thoughts, Biological Systems – The Application of Modeling Principles to Understanding Biological Systems -- Probability and Statistics -- Foundations -- Energy and Force – The Prime Observables -- Biophysical Forces in Molecular Systems -- Physical Principles: Quantum Mechanics -- Chemical Principles -- Measuring the Energy of a System: Energetics and the First Law of Thermodynamics -- Entropy and the Second Law of Thermodynamics -- Which Way Is That System Going? The Gibbs Free Energy -- The Thermodynamics of Phase Equilibria -- Building a Model of Biomolecular Structure -- Water: A Unique Solvent and Vital Component of Life -- Ion–Solvent Interactions -- Ion–Ion Interactions -- Lipids in Aqueous Solution -- Macromolecules in Solution -- Molecular Modeling – Mapping Biochemical State Space -- The Electrified Interphase -- Function and Action Biological State Space -- Transport – A Non-equilibrium Process -- Flow in a Chemical Potential Field: Diffusion -- Flow in an Electric Field: Conduction -- Forces Across Membranes -- Kinetics – Chemical Kinetics -- Dynamic Bioelectrochemistry – Charge Transfer in Biological Systems -- Methods for the Measuring Structure and Function -- Separation and Characterization of Biomolecules Based on Macroscopic Properties -- Analysis of Molecular Structure with Electronic Spectroscopy -- Molecular Structure from Scattering Phenomena -- Analysis of Structure – Microscopy -- Epilogue -- Physical Constants.
Keywords: Biochemistry; Biophysics; Biological physics; Physical chemistry; Medicine; Biochemistry, general; Biological and Medical Physics, Biophysics; Physical Chemistry; Biomedicine, general